Human cells lacking CDC14A and CDC14B show differences in ciliogenesis but not in mitotic progression - Partscht, Patrick; Uddin, Borhan; Schiebel, Elmar (Journal of cell science, 2021)
The budding yeast phosphatase Cdc14 has a central role in mitotic exit and cytokinesis. Puzzlingly, a uniform picture for the three human CDC14 paralogues CDC14A, CDC14B and CDC14C in cell cycle control has not emerged to date. Redundant functions between the three CDC14 phosphatases could explain this unclear picture. To address the possibility of redundancy, we tested expression of CDC14 and analysed cell cycle progression of cells with single and double deletions in CDC14 genes. Our data suggest that CDC14C is not expressed in human RPE1 cells, excluding a function in this cell line. Single- and double-knockouts (KO) of CDC14A and CDC14B in RPE1 cells indicate that both phosphatases are not important for the timing of mitotic phases, cytokinesis and cell proliferation. However, cycling CDC14A KO and CDC14B KO cells show altered ciliogenesis compared to wild-type cells. The cilia of cycling CDC14A KO cells are longer, whereas CDC14B KO cilia are more frequent and disassemble faster. In conclusion, this study demonstrates that the cell cycle functions of CDC14 proteins are not conserved between yeast and human cells.
Gesehen am 31.03.2021